2013
DOI: 10.1016/j.ejim.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoea is not the only symptom that needs to be treated in patients with microscopic colitis

Abstract: Diarrhoea is not the only symptom that needs to be treated in patients with microscopic colitis. Link to publication Citation for published version (APA): Roth, B., Bengtsson, M., & Ohlsson, B. (2013). Diarrhoea is not the only symptom that needs to be treated in patients with microscopic colitis. European Journal of Internal Medicine, 24(6), 573-578. DOI: 10.1016573-578. DOI: 10. /j.ejim.2013 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…Nevertheless, in light of the current knowledge on MC, a colonic, epithelial dysfunction seems more pertinent in the pathophysiology of MC than autoimmunity 31. Intestinal ischemia, drugs, and environmental factors, such as smoking, may trigger mucosal changes which could represent an intestinal reaction to diverse irritants rather than being a specific entity 12,32…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in light of the current knowledge on MC, a colonic, epithelial dysfunction seems more pertinent in the pathophysiology of MC than autoimmunity 31. Intestinal ischemia, drugs, and environmental factors, such as smoking, may trigger mucosal changes which could represent an intestinal reaction to diverse irritants rather than being a specific entity 12,32…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was associated with patients fulfilling both the criteria for IBS-like symptoms and MC, and not with pure MC [Roth et al 2013a[Roth et al , 2014. It remains to be determined whether smoking causes IBS, with the ensuing need of a colonoscopy whereby microscopic inflammation can occasionally be found, or whether smoking induces true MC.…”
Section: Discussionmentioning
confidence: 99%
“…When scrutinizing all medical records in several districts of Sweden, it was found that the majority of patients had had only a single attack of MC [Olesen et al 2004a;Roth et al 2013a;Thörn et al 2013]. The same rule as for IBD should be introduced with respect to MC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations